Everyday state and politics in India : government in the backyard in Kalahandi - Routray, Sailen (Routledge/Edinburgh South Asian studies series., 2018)
"The Kalahandi district in the state of Odisha in Eastern India is regarded as an iconic region of underdevelopment and is often perceived to be the 'Somalia' of the country. It is also the site of a large number of governmental interventions. This book focuses on governance in the state of Odisha and provides an ethnographic account of the changing forms of governmental actions in the development sector. It analyses the implementation of WORLP (Western Orissa Rural Livelihoods Project), a new generation watershed-based development project in Kalahandi district in Odish. It shows the morphings of the forms of the state on the ground and the ways in which it is perceived by the agents and objects of statist actions. Arguing that the changes in the institutions and practices of the state in India over the last three decades are better understood through the conceptualisation of state-fabrication, rather than of state-formation, the author describes five governmental tactics related to emergent modes of governmental action in the context of watershed development in Kalahandi . The book identifies an increasing convergence in the everyday practices of governmental and non-governmental organisations, and the growth of 'the social' as a terrain and object of governmental action as two important effects of the process of deployment of these tactics. Providing an alternative analysis of state and politics in India, this book adds to the literature surrounding the everyday state by illuminating recent changes in state-society relations. It will be of interest to academics in the field of Political Science, Public Policy, Development Studies, Social Anthropology/Sociology and South Asian studies"--